The wrong t‐shirt: configurations of language and identity at Warruwi Community. (19th February 2018) - Singer, Ruth
Abstract : On June 22nd 1916, Reverend James Watson was brought to Warruwi in a canoe by a group of Maningpurru people. A re‐enactment of this event was staged at the beach called Angpungijpa or Watson's Landing on the 22nd of June 2016. The performers wore either a yellow or blue t‐shirt and the two colours were interpreted by many participants as representing the languages Mawng and Kunwinjku. In interpreting the t‐shirts, people made a direct connection between language and identity, invoking the 'language tribe' (Rumsey 1993). In other contexts, however, language ownership is claimed by connecting language to identity indirectly, via patrilineal clan (Merlan 1981). The multiple configurations of language and identity available at Warruwi reflect the way that clan groupings, significant within the current regime of recognition in the region (Povinelli2002 ) co‐exist with the 'language tribes' of earlier eras and other groupings both long‐standing and emergent.